2023
DOI: 10.1021/acs.est.2c08831
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Glucocorticoid Mediates the Association between Prenatal Per- and Polyfluoroalkyl Substance Exposure and Neonatal Growth Index: Evidence from a Birth Cohort Study

Abstract: Glucocorticoid plays a key role in the growth and organ maturation of fetus. However, the effect of glucocorticoid on the association between per-and polyfluoroalkyl substance (PFAS) exposure and fetal growth is still unknown. We detected cord cortisol (active glucocorticoid in human) and 34 PFAS concentrations in the maternal serum samples, which were collected from 202 mother-fetus pairs in the Maoming Birth Cohort from 2015 to 2018. The mediation effect of cord cortisol on the association between maternal P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…33 Exposure is associated with hypertensive disorders of pregnancy including preeclampsia, [34][35][36] as well as population-level alterations in childhood growth and development. 37,38 Among the catalogue of risks, there is increasing evidence that PFAS accumulate in liver and that liver is a primary target organ for the toxic effects of PFAS. [39][40][41] PFAS and Clinical Biomarker data of Liver Function: A systematic review of 23 relevant human studies in multiple geographies found evidence of adverse effects on liver enzymes and incorporated data from eight adult studies in formal metaanalysis of the historic longer chain compounds.…”
Section: Introductionmentioning
confidence: 99%
“…33 Exposure is associated with hypertensive disorders of pregnancy including preeclampsia, [34][35][36] as well as population-level alterations in childhood growth and development. 37,38 Among the catalogue of risks, there is increasing evidence that PFAS accumulate in liver and that liver is a primary target organ for the toxic effects of PFAS. [39][40][41] PFAS and Clinical Biomarker data of Liver Function: A systematic review of 23 relevant human studies in multiple geographies found evidence of adverse effects on liver enzymes and incorporated data from eight adult studies in formal metaanalysis of the historic longer chain compounds.…”
Section: Introductionmentioning
confidence: 99%